Formation of Early Dissident Movements Ideology in USSR in 1960s Years: Ethics of Alexander Yesenin-Volpin - A. A. Gross (Научный диалог, 2022)
The problem of the appearance of the Soviet dissident movement in 1965 is investigated. Particular attention is paid to the “Glasnost rally” on December 5, 1965, which, according to the recollections of the dissidents themselves, became the “assembly point” of the movement. The novelty of the research lies in the fact that the author offers an interpretation of the moral motives of the initiator of the rally, Alexander Yesenin-Volpin. The main sources of the study are the unpublished diaries of 1961—1965 and the political statement of Yesenin-Volpin in August 1965, kept in the archives of the International Memorial in Moscow.  Particular attention is paid to the case of the publication of the “letter of repentance” by the well-known Moscow dissenter Alexander Ginzburg in the newspaper “Vechernyaya Moskva” in June 1965; it had not previously attracted the attention of researchers. It is shown that, having condemned the “repentance” of a dissenter in a political statement in August 1965, Yesenin-Volpin formulated a “dissident” ethic known in the late 1960s — early 1970s. It has been proven that the statement summed up the dissident’s moral reflections in his diaries and became the source of the slogans with which Yesenin-Volpin was preparing for the «Glasnost Rally». As a result of the study, the author comes to the conclusion that in the summer of 1965 in the imagination of the dissident there was already a social community united by “dissident” values.